Communication in the classroom: practice and reflection of a mathematics teacher - Martinho, Maria Helena (2008)
This paper discusses the conceptions, practices and reflections about practices of a basic education mathematics teacher in Portugal with respect to communication in the mathematics classroom. It also addresses their change through her work on a collaborative project. The case study of this teacher was carried out as part of a long term (one year and a half) collaborative project involving a researcher and three mathematics teachers. The case pro-vides evidence of the relevance of such a project to develop the teacher’s understanding of communication processes in her classroom, putting practices under scrutiny and developing richer communication patterns between teacher and students.